Preliminary Studies on the Occurrence and Abundance of Zooplankton Major Taxa in Keamari, Karachi- Backwaters - Ali, Qadeer Mohammad; Azmi, M. Arshad (Journal of Basic & Applied Sciences, 2017)
A preliminary study was conducted on the occurrence and abundance of zooplankton in the Karachi backwaters. Zooplankton sampling was conducted on monthly basis and the study was carried out on the basis of three seasons including pre-monsoon (January to May), monsoon (June to September) and post-monsoon (October to December) from a permanent station Napier Mole bridge (24o50’34’’.90 N, 66o59’17’’.55 E) during June 1996 to May 1998. The hydrographic parameters including air temperature (oC), water temperature (oC), salinity (ppt), dissolved oxygen (mg/L), pH, and transparency (cm) were recorded. Total 14 groups of zooplankton were recorded; hydromedusae, copepoda, mysids, amphipoda, acetes, lucifer, chaetognath, penaeid pl, caridean pl, zoea, megalopa, squilla larvae, fish larvae, fish eggs and others. Pre-monsoon season shows highest number of individuals and copepods were found to be the dominant group in all seasons. Zooplankton diversity, equitability and margalef index were measured seasonally. Highest shannon – wiener diversity index H’ = (1.83), equitability E= (0.69) and margalef species richness Index d= (1.37) were measured in post-monsoon season. Statistical analysis (ANOVA) was performed in between seasons and zooplanktonic groups. No significant difference (at P>0.05, 0.148) was observed between zooplankton and seasons.